Allport meets internet: A meta-analytical investigation of online intergroup contact and prejudice reduction. (March 2021) - Imperato, Chiara; Schneider, Barry H.; Caricati, Luca; Amichai-Hamburger, Yair; Mancini, Tiziana
Abstract: Since Allport's optimal conditions for reducing prejudice by interpersonal contact were defined, numerous empirical studies have confirmed the efficacy of intergroup contact in reducing prejudice towards outgroups. Given that the Internet is changing the way people communicate and interact daily, it is very possible that the Web plays an important role in reducing prejudice. Assuming that the virtual environment fits Allport boundary conditions for effective contact that reduces prejudice, we undertook this meta-analysis. Our aim was to demonstrate that online intergroup contact is a successful means of improving intergroup relations. Results from 23 studies (20 journal articles and 3 unpublished records) showed that the effect is significant. Effect size was independent of the characteristics of samples, including their countries. There were stronger effects when the induced contact focused on cooperation but not for support of the interaction by an authority figure or the presence of common goals.